2020
DOI: 10.21837/pm.v18i13.778
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Waterfront Development in Lumut City, Perak, Malaysia

Abstract: This study on the evolution of waterfront development in Lumut through physical improvement serves as one component in the formation of a city from the economic, social and environmental aspects. The current study aims to review the elements of urban design that offer an alternative to the revitalisation of the waterfront city in Lumut, Malaysia, particularly to upgrade the physical environment quality and economic vibrancy of cities. The objectives of this study are as follows: (1) examine the consideration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…All of these items can promote the level of user satisfaction and must therefore be managed in the best way possible and distinguished from those in other waterfronts. Isa (2017) suggested that studies related to waterfronts should be improved in terms of the related aspects such as quality of tangible and intangible familiarity and uniqueness by users. Meanwhile, Bakar et al (2016) argued that improving place quality and place identity can attract visitors to visit the area and participate in activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these items can promote the level of user satisfaction and must therefore be managed in the best way possible and distinguished from those in other waterfronts. Isa (2017) suggested that studies related to waterfronts should be improved in terms of the related aspects such as quality of tangible and intangible familiarity and uniqueness by users. Meanwhile, Bakar et al (2016) argued that improving place quality and place identity can attract visitors to visit the area and participate in activities.…”
Section: Discussionmentioning
confidence: 99%
“…To measure place quality, 14 items were developed based on previous studies (Isa, 2017; Nunes and Vale, 2015). These items include location, building design, beautiful landscape, scenery and vista, environment, road design and signboard, accessibility and connectivity, food and drinks, clean air and environment, facilities and amenities, suitable activities, well maintained, goods and services and liveable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operational framework of these rural tourism institutions is carefully designed to prioritize sustainability, foster local development and ensure visitor satisfaction [18]. The Malaysian government regulates these initiatives through ministries by providing guidelines that maintain authenticity and sustainability while encouraging the growth of rural tourism [16].…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to develop a tourism product as attraction, accommodation, food and beverage, destination, activities, and ancillary services, which have been identified as attracting tourists and having a major impact on overall tourist expenditure in previous studies (Chiun, 2019). According to Isa (2020), every improvement or modification that is to be done towards any of the city elements must undergo a proper channel and adhere to improvement or modification steps that design experts have proposed to create harmony between the city elements with their surroundings and further will be able to form an image that has identity, structure and meaning.…”
Section: Introductionmentioning
confidence: 99%